Identifikasi Disfungsi Keluarga pada Lansia yang Tinggal Bersama Keluarga dengan Pengkajian APGAR Keluarga: Identifikasi Disfungsi Keluarga pada Lansia yang Tinggal Bersama Keluarga dengan Pengkajian APGAR Keluarga - Rahmadi, Nida Ashifa; Okvitasari, Yenny; Salsabila, Salsabila; Halimah, Nor; Zinan, Rabiatul (STIKes Hang Tuah Pekanbaru, 2023)
Decreased physical function and accompanying diseases in the elderly will result in dependency and helplessness of the elderly. The role of family can make the elderly experience positive changes in their lives. The family has an informal role for the elderly, namely the family becomes a friend, caregiver, encourager, coordinator, and as peacemaker in caring for the elderly. Therefore, a community service program was carried out to find out family dysfunction in the elderly who live with their families. The study was conducted with pre-elderly and elderly in Musholla Al Anshor (Muslim prayer room), RT. 15, Gang Purnama Pasar Lama, Banjarmasin with 15 respondents. This community service was carried out face-to-face using APGAR family assessment, preparation of tools and rooms and the elderly. It was implemented using the APGAR (Adaptation, Partnership, Growth, Affection, Resolve). Family assessment questionnaire consisted of 3 categories, namely high family dysfunction (0-3), moderate family dysfunction (4-6), and low family dysfunction (7-10). The results of this community service program were obtained from all respondents who had APGAR assessment scores for families with low family dysfunction (100%), moderate family dysfunction (0%), and high family dysfunction (0%). It means that family functions still plays a good role in both the pre-elderly and elderly who live with their families. Abstrak Penurunan fungsi fisik dan penyakit yang menyertainya penyakit usia lanjut akan mengakibatkan ketergantungan dan ketidakberdayaan lansia. Peran keluarga dapat membuat lansia mengalami perubahan positif dalam kehidupannya. Keluarga memiliki peran secara informal bagi lansia yaitu keluarga menjadi sahabat, pengasuh, pendorong, koordinator, dan sebagai pendamai dalam merawat lansia. Untuk itulah program pengabdian masyarakat dilakukan mengetahui disfungsi keluarga pada lansia yang tinggal bersama keluarga. Pengkajian dilakukan dengan pra lansia dan lansia yang ada di Musholla Al Anshor, RT. 15, Gang Purnama Pasar Lama, Banjarmasin dengan responden 15 orang. Pengabdian masyarakat ini dilakukan secara tatap muka menggunakan pengkajian APGAR (Adaptation, Partnership, Growth, Affection, Resolve) keluarga, persiapan alat dan ruangan, dan lansia. Pelaksanaannya dengan menggunakan kuesioner pengkajian APGAR terbagi menjadi 3 kategori yaitu disfungsi keluarga tinggi (0-3), disfungsi keluarga sedang (4-6), dan disfungsi keluarga rendah (7-10). Hasil dari program pengabdian masyarakat ini di dapatkan seluruh responden memilki nilai pengkajian APGAR Keluarga dengan disfungsi keluarga rendah (100%), disfungsi keluarga sedang (0%), disfungsi keluarga tinggi (0%). Artinya, fungsi keluarga masih berperan baik pada pra lansia dan lansia yang tinggal bersama keluarganya.